2016
DOI: 10.1038/ncomms13555
|View full text |Cite
|
Sign up to set email alerts
|

Increased DNA methylation variability in type 1 diabetes across three immune effector cell types

Abstract: The incidence of type 1 diabetes (T1D) has substantially increased over the past decade, suggesting a role for non-genetic factors such as epigenetic mechanisms in disease development. Here we present an epigenome-wide association study across 406,365 CpGs in 52 monozygotic twin pairs discordant for T1D in three immune effector cell types. We observe a substantial enrichment of differentially variable CpG positions (DVPs) in T1D twins when compared with their healthy co-twins and when compared with healthy, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
151
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(159 citation statements)
references
References 73 publications
(102 reference statements)
8
151
0
Order By: Relevance
“…This study identified the methylation state of 88 CpG sites, showing a significant difference in the methylation between the affected and unaffected twins. They also found a marked difference in the DNA methylation of HLA, INS, IL-2RB and CD226 among T1D-discordant MZ twins [15]. Another study across 406,365 CpGs in 52 monozygotic twin pairs discordant for T1D in three immune effector cell types revealed a substantial enrichment of differentially variable CpG positions (DVPs) in T1D twins when compared with their healthy co-twins and healthy unrelated individuals [14].…”
Section: Epigenetic Mechanismmentioning
confidence: 97%
See 3 more Smart Citations
“…This study identified the methylation state of 88 CpG sites, showing a significant difference in the methylation between the affected and unaffected twins. They also found a marked difference in the DNA methylation of HLA, INS, IL-2RB and CD226 among T1D-discordant MZ twins [15]. Another study across 406,365 CpGs in 52 monozygotic twin pairs discordant for T1D in three immune effector cell types revealed a substantial enrichment of differentially variable CpG positions (DVPs) in T1D twins when compared with their healthy co-twins and healthy unrelated individuals [14].…”
Section: Epigenetic Mechanismmentioning
confidence: 97%
“…The global DNA hypomethylation within gene promoter regions may cause T1D, but single CpG sites alone may not contribute to the onset and pathogenesis of T1D [16]. Although twin-studies on type 1 diabetes suggest that the abnormal DNA methylation might act as a pivotal part in the etiology of T1D, hypermethylation in CpG sites of some genes can be also observed in affected discordant twins [15]. Similarly, it was reported that CD14+ and CD4+ cells of T1D quadruplets were hyper-and hypo-methylated [17].…”
Section: Epigenetic Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…13 In addition to genetic predisposition, environmental and epigenetic factors impact the disease susceptibility. 14, 15 …”
mentioning
confidence: 99%